Correlation Between Knowledge, Attitudes and Behavior of General Practitioners in Primary Health Facilities Towards the Diagnosis and Management of Psoriasis - Diska Permai Suri; Suandy Suandy; Rudi Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aimed to evaluate the knowledge, attitude, and behavior of general practitioners regarding the diagnosis and management of psoriasis in Primary Health Care (PHC) settings in Binjai City. A cross-sectional design was employed involving 66 general practitioners recruited through total sampling from PHC facilities in Binjai City. Data analysis was conducted using univariate methods and the Spearman Rho correlation test with a significance level of α = 0.05. The results showed that most general practitioners had insufficient knowledge related to the diagnosis and management of psoriasis. A significant correlation was identified between knowledge and both diagnostic accuracy and management practices (p < 0.001), whereas attitude and behavior were not significantly associated with these outcomes (p > 0.05). In conclusion, improving the knowledge of general practitioners is essential to enhance diagnostic accuracy and management quality of psoriasis in PHC settings. Future research is recommended to utilize different measurement scales to obtain more comprehensive insights